Challenges of promoting human rights in the field of memory in Brazil: analysis of the jurisprudence of the inter-american court - Tavares, Celma (Ius Humani. Jornal do direito, 2025)
In post-dictatorial contexts, such as the Brazilian, the way to make the collective right to know the past makes the difference between the preservation of memory and truth or the choice of oblivion. Thus, it is essential to understand that memory policies are not only related to the past but also to the present and the future as they play a key role in democratization consolidation processes. The purpose of this article is to analyze the jurisprudence of the Inter-American Court in relation to Brazil in the field of memory and truth. To this end, a qualitative approach and content analysis have been used. The Sentences of the case of Gomez Lund and others vs Brazil 2010 and the case of Herzog and others vs. Brazil 2018 make it necessary to investigate and punish serious human rights violations. In fact, both cases concern crimes against humanity, impossible to amnesty and imprescriptible. In addition, the Court states in its case law jurisprudence that the right to memory and truth falls within the framework of the right to access to justice. The Brazilian state has the obligation to comply with both judgments and the duty to carry out the control of conventionality between its internal rules and the American Convention of Human Rights, especially after the attempted coup in 2023.